Multilingual website and cyberconsultations for oromandibular dystonia - Kazuya Yoshida (MDPI AG, 2018)
Oromandibular dystonia is a focal dystonia that manifests as involuntary masticatory and/or tongue muscle contractions. This movement disorder is frequently misdiagnosed as a temporomandibular disorder. Hence, it would be useful to establish a method that makes it possible for patients with the condition to find appropriate medical institutions by themselves. The author produced a website Involuntary movements of the stomatognathic region (https://sites. google.com/site/oromandibulardystoniaenglish/) for patients with oromandibular dystonia, which is available in twenty languages. It has been viewed more than 1,000,000 times by individuals from all over the world. The visitors to the site have completed questionnaires and/or sent images or videos of their involuntary movements over the internet. Cyberconsultations (remote diagnosis) were also performed via Skype™. Approximately 1000 patients with involuntary stomatognathic movements visited our department. Only 12.5% of the patients had previously been diagnosed with or were suspected to have dystonia. The findings of this study suggest that the multilingual website has contributed to increasing awareness of oromandibular dystonia and that the provision of basic telemedicine via the internet can aid the diagnosis and treatment of oromandibular dystonia.